PRE-SERVICE SCIENCE TEACHERS' VIEWS REGARDING COMPUTER-AIDED INSTRUCTION. - ER^, İbrahim; BEKTAŞ, Oktay; ÖNER ARMAĞAN, Fulya; SAYLAN, Aslı (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2015)
Aiming to get pre-service science teachers' views about using computer and computer based instruction in the courses, this research was carried out with the participation of six pre-service science teachers enrolled at Erciyes University, Kayseri. Phenomenology as a qualitative research method was used in the study. In this context, after the literature was reviewed, 13-item interview form was created and a semi-structured interview was conducted for the data collection. The qualitative data were analyzed via descriptive analysis. A science teacher with a six years teaching experience and an expert in the field of science education controlled the analysis process. Taking a number of measures, the validity and reliability of the study were tried to be increased. Overall results obtained in the study were; 'Basic Computer' courses given in the education faculties are inadequate in terms of teaching practice and the training should be more practice-oriented. In addition, according to the findings obtained from all participants, it was reached the conclusion that computer and computerbased instruction should be used in science courses and in this context all pre-service science teachers should be able to use the computer better.